2010
DOI: 10.1177/1753193410364179
|View full text |Cite
|
Sign up to set email alerts
|

Extension fractures of the distal radius in patients older than 50: a prospective randomized study comparing fixation using mixed pins or a palmar fixed-angle plate

Abstract: We randomized 103 patients over the age of 50 with an unstable closed intra- or extra-articular dorsally displaced distal radius fracture to have either palmar fixed-angle plating (n=50) or 'mixed pinning' (n=53) and compared the clinical and radiological outcomes at 3, 6, 12 and 26 weeks after surgery in a prospective study. Postoperative palmar tilt was significantly better in those stabilized with K-wires, but loss of reduction was statistically less in those stabilized with a plate. At 26 weeks, functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 26 publications
6
50
1
Order By: Relevance
“…Despite positive results for internal fixation, debate exists as to whether this technique represents first line treatment for displaced, unstable fractures. Marcheix compared palmar fixed angle locking plate fixation to Kirshner wire fixation in a prospective randomized trial, reporting improved functional results (DASH and Herzog scores), with a plate, with better maintenance of reduction [21]. However, equivalent functional scores have also been reported when comparing locking plate fixation to external fixation [22,23], or to conservative treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite positive results for internal fixation, debate exists as to whether this technique represents first line treatment for displaced, unstable fractures. Marcheix compared palmar fixed angle locking plate fixation to Kirshner wire fixation in a prospective randomized trial, reporting improved functional results (DASH and Herzog scores), with a plate, with better maintenance of reduction [21]. However, equivalent functional scores have also been reported when comparing locking plate fixation to external fixation [22,23], or to conservative treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in wrist extension, pronation, radial deviation, or ulnar deviation at 3 months or final followup. Wrist ROM was reported as an outcome in five trials [12,18,21,29,37], four of which reported sufficient information to enable pooling. Radial deviation and ulnar deviation were reported in only two of these trials [12,37].…”
Section: Functional Outcomesmentioning
confidence: 99%
“…According to US Medicare data, internal fixation is the most common surgical intervention for distal radius fracture in the United States, followed closely by percutaneous pinning with K-wires [3]. To our knowledge, there have been no meta-analyses comparing these two common interventions despite multiple trials on the topic having been published [5,12,18,21,29,30,37].…”
Section: Introductionmentioning
confidence: 99%
“…The objective measures are consistently better with internal fixation, but the outcome measures are very similar between operative and nonoperative treatment groups. 99,[103][104][105] A more specific outcome measure for fracture treatment is needed and is a potential for further study. The DASH outcome measure may not be appropriate for distal radius fractures in the older patient population.…”
Section: Distal Radius Fractures (H Hoyen and S Mears)mentioning
confidence: 99%